Influence of Urban Recreation and Infrastructural Resources on the Development of Tourist Destinations - Solomina, Irina; Tsapuk, Dmitry; Isaeva, Olga; Shadskaja, Irina; Kapustin, Ivan (Anais Brasileiros de Estudos Turísticos, 2022)
The article is devoted to the consideration of socio-economic aspects of the development of urban tourist destinations. A city as a tourist destination is a settlement that possesses a sufficient number of tourist and recreational resources, social infrastructure facilities, at least one type of transport accessibility, positioning itself as a tourist center within the state to which it belongs. Measures for the development of the tourist and recreational sector in tourist cities should provide for a comprehensive solution to the priority problems of the urban development and main tourist zones of cities, further strengthening tourist, excursion, and sanatorium-resort services, expanding the range of recreational and tourist services and creating an appropriate material, technical and personnel base, increasing the volume of income from all type tourist activities in contemporary conditions.